Depression Treatment by Non‐Mental‐Health Providers: Incremental Evidence for the Effectiveness of Listening Visits. Issue 1 (March 2017) - Brock, Rebecca L.; O'Hara, Michael W.; Segre, Lisa S.
Abstract: Maternal depression is a prevalent public health problem, particularly for low‐income mothers of young children. Intervention development efforts, which often focus on surmounting instrumental barriers to care, have not successfully engaged and retained women in treatment. Task‐sharing approaches like Listening Visits (LV) could overcome key instrumental and psychological barriers by leveraging the access of trusted, community caregivers to deliver treatment. A recent randomized controlled trial (RCT) demonstrated the efficacy of LV delivered by non‐mental‐health providers as compared to usual care. The present report presents results from a follow‐up phase of that RCT during which participants who had completed LV were followed for an additional 8 weeks and completed measures of depression and quality of life. In addition, participants who were initially randomized to the wait‐list control group received LV and were assessed. Treatment gains previously observed in participants completing LV were enhanced during the 8‐week follow‐up period. Participants receiving LV during the follow‐up period experienced significant improvement in depressive symptoms. Results demonstrate the sustainability of LV delivered by non‐mental‐health providers, and provide preliminary evidence for the replicability of this approach in a sample of predominately low‐income pregnant women and mothers of young children. Highlights: Significant treatment barriers often prevent depressed low‐income mothers from receiving care. Listening Visits delivered by non‐mental‐health providers are an effective treatment for depression. Listening Visits are considered a culturally attuned, evidenced‐based treatment for depression.